Phenomenological inclusions of Proclamation of God’s Faithfulness in Challenging times through the ‘Corridors’ of Christian Education - Ishola-Esan, Helen Olomu (Advances in Social Sciences Research Journal, 2022)
This paper highlights the necessity of proclaiming God’s faithfulness in challenging times. It attempts to bring to light how leaders such as pastors and Christian educators could demonstrate God's faithfulness at all times, especially in challenging times, anywhere, and with all men. The article makes use of descriptive and phenomenological methodologies/approaches. It presents some faithful attributes of God through biblical evidences and through the sharing of four significant personal experiences. The paper enunciates that proclaiming God’s faithfulness through ‘corridors’ of Christian education are didactic and pragmatic in nature. The paper recommends that Christians, leaders/pastors, Christian educators etc should appreciate, speak of, or declare God’s faithfulness at all times, primarily through their life experiences, calling and professional training, and living a lifestyle that demonstrates the celebration of God’s faithfulness at all times: challenging and pleasant times.